MONETARY AND CREDIT FACTORS OF INCREASING DOMESTIC INVESTMENT DEMAND IN THE RUSSIAN ECONOMY - M. A. Abramova; L. L. Igonina (Финансы: теория и практика)
Topic. The article discusses the trends shaping the domestic investment demand in the Russian economy in the context of the regulatory capacity of monetary and credit policy. Purpose. We try to identify factors and conditions that stimulate investment growth in the Russian economy taking into account the active role of the credit system.Methodology. The study is based on the use of systematic, evolutionary and institutional approaches and the artificial neural network method. To calculate data about the volumes and dynamics of investment loans the authors applied the method of indirect calculation using data from Bank of Russia of loans to non-financial enterprises and the Federal state statistics service on the value of business investment in fixed capital, and the share of Bank loans in total sources of financing investments in fixed capital.Result. We discovered some specific features of the influence of the main channels of the transmission mechanism of modern monetary and credit policy of the Bank of Russia on the formation of internal investment demand. The authors understand it as a need, the willingness and ability of economic agentsresidents to the reproduction and accumulation of capital for economic growth based on innovation. According to the obtained results based on analysis of profitability ratios of goods sold (products, works, and services) of main economic activity and interest rates on Bank deposits we found the negative growth trend in the number of main branches of economy, where profitability is lower than the weighted average rate on deposits.Conclusions. We made some suggestions as concerns improving the effects of current monetary and credit policy in the context of forming of internal investment demand. Also, we grounded the principles of choice of strategic priorities of monetary and credit policy adequate to the requirements of sustainable economic growth and interrelated with other components of the macroeconomic policy.